Eugenol eliminates carbapenem-resistant Klebsiella pneumoniae via reactive oxygen species mechanism - Liu, Wei; Chen, Guang; Dou, Keke; Yi, Bingcheng; Wang, Danyang; Zhou, Qihui; Sun, Yunbo (Frontiers in Microbiology, 2023)
Multidrug-resistant (MDR) bacterial infections have gained increasing attention due to the high incidence rates and high mortality, especially for the carbapenem-resistant Klebsiella pneumoniae (CRKP) infection that can cause severe complications (e.g., pneumonia and sepsis) in multiple organs. Given the excellent antibacterial/biofilm activity of eugenol (EG) against CRKP, this study mainly explored the underlying mechanism of EG-mediated antibacterial/biofilm situation in CRKP from the aspect of ROS. Bacteria growth and biofilm formation evaluation verified the excellent antibacterial ability of EG against planktonic CRKP. Scanning electron microscopy (SEM), transmission electron microscopy (TEM), and O-Nitrobenzene β-D-galactoside (ONPG) tests demonstrated that EG eliminated the CRKP via destroying the bacteria's membrane permeability. Lastly, detection of ROS production and cytoplasmic component leakage showed that EG could induced the high ROS expression of CRKP to break the bacteria’s membrane and inhibit biofilm formation, which ultimately resulted in bacterial death. Overall, this work verified that EG could eliminated CRKP via ROS-induced membrane rupture and biofilm inhibition, which offers vital evidences to explain the antibacterial ability of EG against CRKP.